Substrate comprising tantalum coating

Through the vapor deposition method, a process gas containing halide substances and tantalum sources is used to deposit a tantalum carbide coating at high temperature, solving the problems of layer separation and excessive expansion of tantalum carbide in pores, and improving the chemical resistance and mechanical properties of the carbonaceous substrate.

CN119585227APending Publication Date: 2025-03-07SGL CARBON SE
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202380055955.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art When depositing a tantalum carbide coating, it is easy to cause layer separation and excessive expansion of tantalum carbide in the pores, damaging the graphite substrate.

Method used

By using the vapor deposition method, the carbonaceous substrate is controlled to heat the carbonaceous substrate at high temperature by supplying process gas containing halide substances and tantalum source to the reaction chamber, ensuring anchorage of the tantalum carbide coating on the substrate, and forming a partially filled tantalum carbide pore coating in the holes.

Benefits of technology

It effectively prevents separation and damage caused by the mismatch between the thermal expansion of the tantalum carbide coating and the graphite substrate, and improves the chemical resistance and mechanical properties of the carbonaceous substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585227A_ABST
    Figure CN119585227A_ABST
Patent Text Reader

Abstract

In a first aspect, the present disclosure relates to a vapor deposition method of coating a carbonaceous substrate with a tantalum carbide coating, where the method includes a coating step. The coating step includes placing the carbonaceous substrate in a reaction chamber and heating the reaction chamber to a temperature between about 1100 DEG C and about 1500 DEG C for a duration of about 1 hour to about 24 hours. The coating step further includes supplying a process gas to the reaction chamber, where the process gas comprises a halide-containing species, and where the process gas comprises less than 4 atomic% carbon and less than 10 vol% H2 within at least 15 minutes after the start of the process. Further, the coating step includes supplying a tantalum-containing substance to the reaction chamber, or placing a tantalum-containing solid into the reaction chamber. Alternatively, the method includes placing a solid comprising a tantalum halide into the reaction chamber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of tantalum carbide coated substrates. More specifically, the present invention relates to a carbonaceous substrate coated with a tantalum carbide coating. Background Art

[0002] Due to its high temperature resistance, especially high melting point and thermal conductivity, as well as low thermal expansion coefficient, graphite can be used in many high temperature processes. In addition, graphite can be used as a susceptor. A susceptor can absorb electromagnetic energy and convert it into heat or re-emit electromagnetic energy as infrared thermal radiation. Due to its function as a susceptor, relatively high chemical purity and high temperature resistance, graphite can be used as a wafer carrier in the semiconductor industry. For example, a wafer carrier can be used to grow GaN layers on a wafer by metal organic vapor phase epitaxy (MOVPE) to produce blue light emitting diodes (LEDs) or high electron mobility transistors (HEMTs).

[0003] In addition, graphite can be used as a crucible material in physical vapor transport processes of semiconductor materials such as SiC. Due to its high temperature stability, graphite crucibles can be used over a wide temperature range. In addition, the high thermal conductivity of graphite can more accurately control the temperature of the material located within the graphite crucible, thereby allowing controlled growth of semiconductor crystals for subsequent wafer dicing. Specifically, the high thermal conductivity of graphite can allow a temperature gradient to be applied to the material located within the crucible while reducing temperature hysteresis.

[0004] However, because graphite contains or consists primarily of carbon, it can be susceptible to chemical attack. For example, graphite can be attacked by hydrogen or ammonia used in semiconductor production. In addition, graphite can still contain contaminants such as boron, which can be undesirably transferred to semiconductor wafers during high-temperature processes. In fact, carbon itself can be a contaminant in many semiconductor processes.

[0005] In addition, the surface of graphite may release graphite particles, which may damage the wafer or the film grown on the wafer. For example, when the wafer located therein moves (e.g., rotates), the surface of graphite may release graphite particles. In order to increase chemical resistance, mechanical resistance, and seal contaminants and particles in the graphite, a coating can be applied to the surface of the graphite. In particular, metal carbide coatings (e.g., tantalum carbide coatings) can be used to increase the chemical resistance of graphite and seal its surface. However, known processes for depositing tantalum carbide on wafer carriers may cause the layer to easily delaminate from the underlying graphite. It is believed that delamination may occur due to the different thermal expansion coefficients of the tantalum carbide coating and the graphite substrate. In addition, some processes may cause tantalum carbide to completely fill the pores of the porous graphite substrate. Due to the different thermal expansion coefficients of tantalum carbide and the graphite substrate, the tantalum carbide in the pores may over-expand relative to the surrounding graphite substrate, which may cause localized damage to the graphite substrate.

[0006] The present disclosure is directed to solving the above-mentioned problems in substrates comprising tantalum carbide coatings. Summary of the invention

[0007] method

[0008] In a first aspect, the present disclosure relates to a vapor deposition method for coating a carbonaceous substrate with a tantalum carbide coating, wherein the method includes a coating step. The coating step includes placing the carbonaceous substrate in a reaction chamber, heating the reaction chamber to a temperature between about 1100°C and about 1500°C for a duration of about 1 hour to about 24 hours. The coating step also includes supplying a process gas to the reaction chamber, wherein the process gas contains a halide-containing substance, and wherein the process gas contains less than 4 atomic % carbon and less than 10 volume % H2 within at least 15 minutes after the start of the process. In addition, the coating step includes supplying a tantalum-containing substance to the reaction chamber, or placing a solid containing tantalum in the reaction chamber. Alternatively, the method includes placing a solid containing a tantalum halide in the reaction chamber.

[0009] In some embodiments, the solid comprising tantalum or tantalum halide may be in the form of a powder.

[0010] In some embodiments, the solid comprising tantalum may include tantalum in metallic form.

[0011] In some embodiments, the tantalum-containing species and the halide-containing species may be the same, in particular the process gas may contain TaCl 5 .

[0012] In some embodiments, the solid containing tantalum halide may include TaCl5 and / or other TaCl x Physical form of tantalum halides.

[0013] In some embodiments, the coating step may include a first coating step and a second coating step, wherein the first coating step is performed at a first temperature and the second coating step is performed at a second temperature, in particular wherein the first temperature may be lower than the second temperature.

[0014] In some embodiments, the first temperature may be between about 1150°C and about 1250°C and / or the second temperature may be between about 1250°C and about 1350°C.

[0015] In some embodiments, the coating step may include a third coating step, wherein the third coating step may be performed at a third temperature, in particular wherein the third temperature is higher than the first temperature and / or the second temperature.

[0016] In some embodiments, the third temperature may be at least about 1350°C, more specifically between about 1350°C and about 1600°C, and particularly between about 1350°C and about 1450°C.

[0017] In some embodiments, the duration of the first coating step and / or the second coating step may each be at least about 15 minutes, more specifically between about 30 minutes and about 120 minutes, and especially between about 45 minutes and about 90 minutes.

[0018] In some embodiments, the duration of the third coating step can be at least about 60 minutes, more specifically at least about 180 minutes, and especially at least about 300 minutes.

[0019] In some embodiments, the process gas in the first coating step may contain less than 4 atomic %, more specifically less than 1 atomic %, and especially less than 0.1 atomic % carbon relative to the total atoms in the process gas.

[0020] In some embodiments, the process gas in the first coating step may contain less than 4 vol. %, more specifically less than 1 vol. %, and especially less than 0.1 vol. % H 2 relative to the total volume of the process gas.

[0021] In some embodiments, the process gas in the first coating step may contain a halide, particularly chlorine, in a maximum ratio of halide to carbon of 1:0.05, more particularly 1:0.01, and especially 1:0.001.

[0022] In some embodiments, the process gas in the first coating step may contain a halide, particularly chlorine, in a maximum ratio of halide to H 2 of 1:0.05, more particularly 1:0.01, and especially 1:0.001.

[0023] In some embodiments, the process gas in the second coating step may contain more than 0.1 atomic %, more specifically more than 1 atomic %, and especially more than 4 atomic % carbon relative to the total number of atoms in the process gas.

[0024] In some embodiments, the process gas in the third coating step may contain more than 0.1 atomic %, more specifically more than 1 atomic %, and especially more than 4 atomic % carbon relative to the total number of atoms in the process gas.

[0025] In some embodiments, the halide-containing substance may be a chloride-containing substance, more specifically wherein the chloride-containing substance may be Cl2 or HCl, and in particular wherein the halide-containing substance may be HCl.

[0026] In some embodiments, the process gas may also contain an inert gas, more specifically nitrogen or argon, and especially argon.

[0027] In some embodiments, the pressure in the reaction chamber may be between about 0.001 bar and about 1.1 bar, more specifically between about 0.001 bar and about 0.5 bar, and especially between about 0.1 bar and about 0.2 bar.

[0028] In some embodiments, the method may further include an annealing step after the coating step.

[0029] In some embodiments, the annealing step may include placing the coated carbonaceous substrate into an annealing chamber, heating the annealing chamber to a temperature between about 900°C and about 1800°C, more specifically between 1200°C and about 1500°C, for a duration of about 10 minutes to about 5 hours, and supplying a process gas to the reaction chamber, wherein the process gas may contain a carbon-containing substance, more specifically a carbon and hydrogen-containing substance, and in particular C2H4.

[0030] In some embodiments, the annealing step may include placing the coated carbonaceous substrate into an annealing chamber and heating the chamber to a temperature between about 1900° C. and about 2300° C. under an inert gas atmosphere for a duration of about 0.5 hours to about 3 hours.

[0031] Substrate

[0032] In a second aspect, the present disclosure is directed to a carbonaceous substrate comprising a first tantalum carbide coating, wherein the first tantalum carbide coating is located on an outer surface of the carbonaceous substrate, and wherein the carbonaceous substrate comprises a plurality of pores, the plurality of pores comprising a TaC porous coating, wherein the plurality of pores are not completely filled with the tantalum carbide porous coating.

[0033] In some embodiments, the plurality of holes may be arranged less than 182 μm, in particular less than 100 μm from the outer surface.

[0034] In some embodiments, the thickness of the TaC porous coating may be less than 20 μm, more specifically less than 10 μm, and especially less than 8 μm.

[0035] In some embodiments, the thickness of the TaC pore coating between about 20 μm and about 60 μm in depth may be between about 0.5 μm and about 8 μm, more specifically between about 0.8 μm and about 3 μm, and particularly between about 1 μm and about 2.5 μm.

[0036] In some embodiments, the ratio of the thickness of the first tantalum carbide coating layer to the thickness of the tantalum carbide porous coating layer having a depth between about 20 μm and about 60 μm can be between about 2:1 and about 30:1, more specifically between about 3:1 and about 20:1, and especially between about 5:1 and about 15:1.

[0037] In some embodiments, the maximum diameter of the plurality of pores may be between about 5 μm and about 100 μm, more specifically between about 10 μm and about 50 μm, and particularly between 15 μm and about 25 μm.

[0038] In some embodiments, among the plurality of pores exhibiting a maximum diameter between about 5 μm and about 100 μm, at least 50%, more specifically at least 75%, and especially at least 90% of the pores may not be completely filled by the tantalum carbide porous coating.

[0039] In some embodiments, the volume of the plurality of pores in the carbonaceous substrate may be between about 1 vol % and about 20 vol %, more specifically between about 5 vol % and about 15 vol %, and particularly between about 7 vol % and about 13 vol %.

[0040] In some embodiments, the carbonaceous substrate may include TaC having a penetration depth of at least 20 μm, more specifically at least 40 μm, and especially at least 60 μm.

[0041] In some embodiments, the first tantalum carbide coating and / or the tantalum carbide porous coating may have a ratio of Ta to C between about 1.3:1 and about 1:1.3, more specifically between about 1.1:1 and about 1:1.1, and especially between about 1.05:1 and about 1:1.05.

[0042] In some embodiments, the thickness of the first tantalum carbide coating may be between about 0.1 μm and about 40 μm, more preferably between about 5 μm and about 35 μm, and particularly between about 10 μm and about 30 μm.

[0043] In some embodiments, the first tantalum carbide coating may include tantalum carbide in the form of tantalum carbide crystals, wherein each tantalum carbide crystal orientation in the group

[111] ,

[200] ,

[220] ,

[311] , and

[311] exhibits a texture coefficient TC between about 0.5 and about 1.5. i , the texture coefficient TC i It is calculated from the maximum peak intensity of the x-ray diffraction pattern detected with Cu k-alpha radiation at a wavelength of 1.5406 Å according to the following formula:

[0044]

[0045] Among them I i Accordingly, the maximum intensity of the crystal orientation is selected,

[0046] Where n=5, and

[0047] I 111 is the maximum intensity at 2θ ranging from 33.9° to 35.9°,

[0048] I 200 is the maximum intensity at 2θ ranging from 39.4° to 41.4°,

[0049] I 220 is the maximum intensity at 2θ ranging from 57.6° to 59.6°,

[0050] I 311 is the maximum intensity at 2θ ranging from 69.0° to 71.0°,

[0051] I 222 is the maximum intensity at 2θ ranging from 72.6° to 74.6°,

[0052] And wherein if the crystal orientation of the tantalum carbide crystals is random, then I i,0 is the expected strength of the crystal orientation.

[0053] In some embodiments, the porosity of the first tantalum carbide layer may be less than 5 volume %, more specifically less than 1 volume %, and particularly less than 0.1 volume %.

[0054] In some embodiments, the first tantalum carbide layer may contain less than 1 atomic %, more specifically less than 0.1 atomic %, and especially less than 0.01 atomic % of impurities.

[0055] In some embodiments, the carbonaceous substrate comprises, consists essentially of, or consists of graphite.

[0056] In some embodiments, the carbonaceous substrate may include a second tantalum carbide coating, wherein the second tantalum carbide coating may be disposed adjacent to the first tantalum carbide coating, particularly wherein the first tantalum carbide coating may be located between the second tantalum carbide coating and an outer surface of the carbonaceous substrate.

[0057] use

[0058] In a third aspect, the present disclosure relates to the following use of a carbonaceous substrate according to any of the preceding items: the carbonaceous substrate is used as a component of an epitaxial growth system, more specifically as a component of a GaN or SiC growth system, and in particular as a wafer carrier for a GaN or SiC growth system; or, as a component of a physical vapor transport (PVT) system, more specifically as a component of a SiC PVT physical vapor transport system, and in particular as a crucible or hot wall for a PVT system. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The experimental setup for the first and sixth experiments is shown.

[0060] Figure 2 The surface morphology of the samples obtained from the first and second experiments is shown.

[0061] Figure 3 Partially coated wells from the third (c), fourth (b), and fifth (a) experiments are shown.

[0062] Figure 4 The experimental setup for the third and fourth experiments is shown.

[0063] Figure 5 The surface morphology of the sample obtained from the third experiment is shown.

[0064] Figure 6 The surface morphology of the sample obtained in the fourth experiment is shown.

[0065] Figure 7 The surface morphology of the sample obtained in the fifth experiment is shown.

[0066] Figure 8 The surface morphology of the sample obtained in the sixth experiment is shown.

[0067] Fig. 9 The surface morphology of the sample obtained in the eighth experiment is shown.

[0068] Fig.10 Shown are the X-ray diffraction results of the sample obtained in the seventh experiment.

[0069] Fig.11 The penetration depths obtained in the third, fourth, and fifth experiments are shown.

[0070] Fig.12 The coating thickness is shown relative to the coating depth.

[0071] Fig.13 Shown are the X-ray diffraction results of the sample obtained in the sixth experiment.

[0072] Fig.14 Shown are the X-ray diffraction results of the sample obtained in the eighth experiment.

[0073] Fig.15 Shown are the X-ray diffraction results of the sample obtained in the eighth experiment.

[0074] Fig.16 Shown are the X-ray diffraction results of the sample obtained in the ninth experiment. DETAILED DESCRIPTION OF THE INVENTION

[0076] The disclosure will be described in detail below. The terms or words used in the specification and various aspects of the disclosure should not be interpreted restrictively as having only ordinary language or dictionary meanings, unless otherwise clearly defined in the following specification, otherwise they should be interpreted as having their ordinary technical meanings determined in the relevant technical field. The detailed description will refer to specific embodiments to better illustrate the disclosure, but it should be understood that the disclosure is not limited to these specific embodiments.

[0077] method

[0078] As previously mentioned, it is believed that delamination of the tantalum carbide coating on the graphite substrate may occur due to the difference in thermal expansion coefficients of the tantalum carbide coating and the graphite substrate and insufficient "anchoring" of the tantalum carbide coating in the graphite substrate. In addition, some processes may cause the tantalum carbide to fill the pores of the porous graphite substrate. Due to the difference in thermal expansion coefficients of the tantalum carbide and the graphite substrate, the tantalum carbide in the pores may over-expand relative to the surrounding graphite substrate, which may cause localized failure of the graphite substrate.

[0079] Tantalum carbide naturally comprises tantalum and carbon, and known processes for depositing tantalum carbide on a substrate typically use a tantalum source and a carbon source. The tantalum source and the carbon source may also be present in the form of a single molecule. Surprisingly, it has been found that a tantalum carbide coating can be grown on a carbonaceous substrate using a tantalum halide when the concentration of carbon and hydrogen in the process gas is low. The tantalum halide may be provided to the reaction with the process gas or generated in the reaction chamber. Without being bound by theory, the tantalum halide may then react with the carbon of the carbonaceous substrate, resulting in the formation of tantalum carbide on the carbonaceous substrate without the presence of a large amount of a carbon source in the process gas. Since the tantalum carbide is formed directly from the carbon provided by the carbonaceous substrate, the anchoring of the tantalum carbide coating to the carbonaceous substrate may be improved.

[0080] In addition, it has been observed that the resulting coating may also be present in the pores of the carbonaceous substrate, but will not completely fill the pores. Still not bound by theory, it is theoretically possible that the growth of the tantalum carbide coating on the carbonaceous coating may be limited by the contact of the halide species with the carbon of the carbonaceous substrate. When the tantalum carbide coating is formed from a gas phase containing a large amount of carbon source and tantalum source in a conventional process, the tantalum carbide coating may be formed primarily at the outer surface of the substrate, which may also cause any passages leading to the pores below the outer surface to be quickly blocked, resulting in poor anchoring of the tantalum carbide coating. Additionally or alternatively, in addition to the unfilled pores, the pores, especially those close to the surface, may be overfilled, which may then lead to local damage as described above.

[0081] In addition, the presence of a large amount of hydrogen H2 in the process gas may prevent the formation of TaC. Specifically, the presence of H2 in the process gas may lead to the formation of metallic tantalum on the surface of the carbonaceous substrate, which may require subsequent carburization to obtain a tantalum carbide coating. The term "carburization" refers to the process of reacting precursors (such as pure metals and carbon sources) to obtain carbides (especially metal carbides), such as reacting metallic tantalum with a carbon source to obtain tantalum carbide. Metallic tantalum may also form within the pores of the carbonaceous material and may fill the pores. During the subsequent carburization of the metallic tantalum, its volume may increase, resulting in excessive filling of the pores by tantalum carbide.

[0082] The term "external surface" in the present disclosure may refer to a surface in which no other surface of the carbonaceous substrate is arranged in a direction perpendicular to the surface. Alternatively or in addition, the term "external surface" in the present disclosure may refer to a surface in which at least one reference point on the surface is not surrounded by at least 50% by a wall segment extending away from the body. Alternatively or in addition, the term "external surface" may refer to a surface in which at least one reference point on the surface is not surrounded by a wall segment having a height of at least 1 cm extending away from the body, the wall segment being within a radius of at least 2.5 cm, more specifically at least 3.5 cm and particularly at least 4 cm. For example, the carbonaceous substrate may include a disc-shaped recess, wherein the radius of the recess is 100 mm. The interior of the recess may still be considered an outer surface rather than a depression.

[0083] Furthermore, the term "wall segment" refers to a portion of a wall, more specifically a portion of a wall having a length of at least 100 μm, and in particular a portion of a wall having a length of at least 100 μm and a width of at least 10 μm. The width may also be measured along a curved wall segment, along a curved surface.

[0084] It has been found that by providing tantalum in the form of tantalum halide and carbon from a carbonaceous substrate, the formation of the tantalum carbide coating may not occur primarily at the outer surface because the growth of the tantalum carbide coating slows down as the thickness of the tantalum carbide coating increases. Therefore, the tantalum halide can penetrate into the pores and also form a tantalum carbide porous coating in the pores. In addition, since the formation of the tantalum carbide coating slows down as the thickness increases, the tantalum carbide coating can be prevented from overfilling the pores, resulting in only partial filling of the pores. In addition, although the tantalum halide can initially enter the pores, as the tantalum coating grows on the outer surface, the access to the pores may be blocked, thereby preventing the tantalum carbide porous coating from overgrowing.

[0085] Thus, in a first aspect, the present disclosure relates to a vapor deposition method for coating a carbonaceous substrate with a tantalum carbide coating, wherein the method comprises a coating step. The coating step comprises placing the carbonaceous substrate in a reaction chamber, heating the reaction chamber to a temperature between about 1100°C and about 1500°C for a duration of about 1 hour to about 24 hours. The coating step further comprises supplying a process gas to the reaction chamber, wherein the process gas comprises a halide-containing substance. In addition, within at least 15 minutes after the process begins, the process gas comprises less than 4 atomic (at.) % carbon and less than 10 volume (vol.) % H2. Tantalum can be introduced into the reaction chamber in three different ways.

[0086] First, the coating step may include supplying a tantalum-containing substance to the reaction chamber. For example, the tantalum-containing substance and the halide-containing substance may be the same, in particular wherein the process gas may contain TaCl5 and / or other TaCl x Substances. TaCl5 and / or other TaCl x The substances can be formed in separate chambers and then supplied to the reaction. For example, TaCl5 and / or other TaCl x The species can be formed by reacting tantalum metal with a halide such as HCl or Cl2 in a separate chamber.

[0087] Alternatively or in addition, the coating step may include placing a solid containing tantalum into the reaction chamber. For example, the solid containing tantalum may include tantalum in metallic form. A halide-containing substance, such as hydrogen chloride, HCl, may be supplied to the reaction chamber via the process gas. The halide-containing substance may then react with the tantalum to form, for example, gaseous tantalum (V) chloride, TaCl5 and / or other TaCl x Then, TaCl5 and / or other TaCl x The material can react with the carbonaceous substrate to form a tantalum carbide coating and chlorine gas, Cl2. Other TaCl xThe substance may be, for example, tantalum (IV) chloride, TaCl4, or tantalum (III) chloride, TaCl3. The solid may be, for example, a solid plate of metallic tantalum. Alternatively, the solid may be a powder comprising metallic tantalum. The powder may exhibit a higher specific surface area than the plate and may therefore react with the halide at a higher rate.

[0088] The term "process gas" shall refer to all gases supplied to the reaction chamber. For example, the reaction chamber may include one gas inlet, and the term "process gas" may refer to the entire gas flow supplied into the reaction chamber by the one gas inlet. In another example, the reaction chamber may include multiple gas inlets, wherein all gases supplied to the reaction chamber through the multiple gas inlets shall be considered "process gas". The term "process gas" may also include precursor gases formed within the reaction chamber. For example, if the reaction chamber includes a tantalum halide solid, the term "process gas" may also include gaseous tantalum halide produced from the tantalum halide solid.

[0089] Additionally or alternatively, the solid containing tantalum halide may include TaCl5 and / or other TaCl x Physical form of tantalum halides. TaCl x It may evaporate due to the increased temperature in the reaction chamber and then react with the carbonaceous substrate. TaCl x It may also be in powder form. When the tantalum halide solid is placed in the reaction chamber, the process gas may also contain less than 4 atomic % carbon and less than 10 volume % H2 for at least 15 minutes after the process begins.

[0090] Alternatively, when using solid TaCl placed in the reaction chamber x When using TaCl x When the reaction chamber is sealed, the reaction chamber can be pre-filled with a process gas containing less than 4 atomic % carbon and less than 10 volume % H2 because the tantalum-containing species and the halide-containing species are already present in the reaction chamber.

[0091] Alternatively, when using gaseous TaCl x (e.g. TaCl5), the reaction chamber can be filled with TaCl x and an inert gas (e.g. argon) and then sealed. Subsequently, the reaction in the reaction chamber can be carried out, for example, for 1 minute to 10 minutes. After the reaction has been carried out, the reaction chamber can be flushed and the TaCl x gas and inert gas, sealing the reaction chamber and carrying out the reaction to repeat the process.

[0092] It should be noted that due to the high temperatures in the reaction chamber or process gas, TaCl5 may decompose into other TaCl xTherefore, when using TaCl5, the process gas may contain multiple or any one of the TaCl x Without being bound by theory, it is conceivable that some TaCl x The material may temporarily form metallic tantalum on the surfaces of the reaction chamber. The metallic tantalum on the surfaces of the reaction chamber may then react with halides (e.g., Cl2) present in the gas within the reaction chamber to again form TaCl x material, then the TaCl x The species may react with carbon from the carbonaceous substrate to form TaC.

[0093] In some embodiments, the coating step may include a first coating step and a second coating step, wherein the first coating step is performed at a first temperature and the second coating step is performed at a second temperature, particularly wherein the first temperature may be lower than the second temperature. As described above, as the thickness of the tantalum carbide coating increases, the reaction of the tantalum halide with the carbonaceous substrate slows down. Without being bound by theory, it is believed that the limiting factor may be the diffusion of carbon from the carbonaceous substrate to the outer surface via the tantalum carbide coating, where carbon can react with the tantalum-containing material. By increasing the temperature, the rate at which carbon diffuses through the carbide coating can be increased, thereby increasing the growth rate of the tantalum carbide coating. By first running the process at a lower first temperature, the tantalum coating can penetrate into the pores more effectively without overfilling the pores. Subsequently, when the coating has been anchored to the carbonaceous substrate and the passage into the pores is partially blocked, a second coating step with a higher second temperature can be performed to increase the growth rate of the tantalum carbide coating on the outer surface.

[0094] As described above, without being bound by theory, it is believed that an improved tantalum carbide coating can be achieved by reacting the carbon contained in the carbonaceous substrate with the tantalum-containing material, rather than providing an additional carbon source in the process gas. Therefore, in some embodiments, the process gas in the first coating step may contain less than 4 atomic %, more specifically less than 1 atomic %, and especially less than 0.1 atomic % carbon relative to the total number of atoms in the process gas. For example, the process gas in the first coating step may contain a halide (particularly chlorine) having a maximum ratio of 1:0.05 to carbon, more specifically 1:0.01, and especially 1:0.001. The maximum ratio refers to the maximum relative amount of carbon. Therefore, a ratio of 1 part chlorine to 1 part carbon should be considered to be higher than a ratio of 1 part chlorine to 0.5 parts carbon. Therefore, a maximum ratio of chlorine to carbon of 1:0.05 refers to all ratios ranging from 1 part chlorine to 0 parts carbon to 1 part chlorine to 0.05 parts carbon.

[0095] In the second coating step, the process gas may also contain less than 4 atomic %, more specifically less than 1 atomic %, and in particular less than 0.1 atomic % carbon relative to the total number of atoms in the process gas. For example, the process gas in the second coating step may contain a halide (in particular chlorine) having a maximum ratio of halide to carbon of 1:0.05, more specifically 1:0.01, and in particular 1:0.001. Thus, an increase in the growth of tantalum carbide may be induced by increasing the temperature.

[0096] Alternatively, an additional carbon source may be added to the process gas in the second coating step to increase the growth rate of the tantalum carbide coating on the outer surface. Since the tantalum carbide coating formed in the first coating step blocks the channel, the carbon source may not be able to significantly penetrate into the pores of the carbonaceous substrate in the second coating step, thereby preventing overfilling of the pores. In addition, the tantalum carbide coating may have been fully anchored into the pores by the first coating step, thereby reducing the risk of delamination, even if the thickness of the carbide coating on the outer surface is increased in the second coating step. Therefore, in some embodiments, in the second coating step, the process gas may contain more than 0.1 atomic %, more specifically more than 1 atomic %, and especially more than 4 atomic % carbon relative to the total number of atoms in the process gas.

[0097] In some embodiments, the process gas in the first coating step may contain less than 4 volume %, more specifically less than 1 volume %, and especially less than 0.1 volume % H 2 relative to the total volume of the process gas. As described above, a large amount of H 2 may prevent the formation of a tantalum carbide coating and may result in the formation of a metallic tantalum coating.

[0098] In some embodiments, the process gas in the first coating step may contain a halide, particularly chlorine, in a maximum ratio of halide to H 2 of 1:0.05, more particularly 1:0.01, and especially 1:0.001.

[0099] In some embodiments, the first temperature may be between about 1150°C and about 1250°C and / or the second temperature may be between about 1250°C and about 1350°C.

[0100] In some embodiments, the duration of the first and / or second coating steps may each be at least about 15 minutes, more specifically between about 30 minutes and about 120 minutes, and especially between about 45 minutes and about 90 minutes.

[0101] In some embodiments, the coating step may include a third coating step, wherein the third coating step may be performed at a third temperature, particularly wherein the third temperature is higher than the first temperature and / or the second temperature. In some embodiments, the third temperature may be at least about 1350°C, more particularly between about 1350°C and about 1600°C, and particularly between about 1350°C and about 1450°C. The third coating step may be employed to further increase the thickness of the tantalum carbide coating on the outer surface, particularly with a significantly increased growth rate. The third coating step may also be performed directly after the first coating step.

[0102] It should be noted that the first, second and third temperatures may not be static. The method may also be carried out under a temperature gradient within the ranges listed above for the first, second and third temperatures. For example, in the first coating step, the temperature may be increased from 1150° C. to 1250° C. within one hour.

[0103] In some embodiments, the duration of the third coating step can be at least about 60 minutes, more specifically at least about 180 minutes, and especially at least about 300 minutes.

[0104] The tantalum carbide coating formed by the first coating step and the second coating step can effectively prevent the tantalum in the process gas from contacting the carbon of the carbonaceous substrate, so an additional carbon source in the process gas may be required in the third coating step. Therefore, in some embodiments, the process gas in the third coating step may contain more than 0.1 atomic %, more specifically more than 1 atomic %, and especially more than 4 atomic % carbon relative to the total number of atoms in the process gas.

[0105] In some embodiments, the halide-containing substance may be a chloride-containing substance, more specifically wherein the chloride-containing substance may be Cl2 or HCl, and in particular wherein the halide-containing substance may be HCl. Cl2 or HCl reacts with metallic tantalum (particularly tantalum metal powder) to form TaCl5 and / or other TaCl x Substances. TaCl5 and / or other TaCl x The substance may react with the carbonaceous substrate to form a tantalum carbide coating.

[0106] In some embodiments, the process gas may additionally contain an inert gas, more particularly nitrogen or argon, and especially argon.

[0107] In some embodiments, the pressure in the reaction chamber may be between about 0.001 bar and about 1.1 bar, more specifically between about 0.001 bar and about 0.5 bar, and especially between about 0.1 bar and about 0.2 bar.

[0108] In some embodiments, the method may additionally include an annealing step after the coating step.

[0109] Tantalum carbide may be present in a stoichiometric ratio of tantalum to carbon that deviates from 1:1 (e.g., pure TaC). For example, the ratio of tantalum to carbon may vary between 1:0.4 and 1:1. Thus, tantalum carbide may be present in a stoichiometric ratio of tantalum to carbon that deviates from 1:1 (e.g., pure TaC). x Tantalum carbide exists in the form of Ta2C, where x varies between 0.4 and 1. Tantalum carbide can also be formed in the form of Ta2C.

[0110] Surprisingly, coating a carbonaceous substrate using the process parameters of the first coating step can produce a tantalum carbide coating in which the ratio of tantalum to carbon is close to 1. However, at higher temperatures, such as above 1500°C, it is observed that the stoichiometry may shift toward a higher proportion of tantalum. Specifically, as the temperature increases and the coating thickness increases, the ratio of Ta2C to metallic tantalum increases. Specifically, the ratio of Ta2C to metallic tantalum is higher in portions of the tantalum carbide coating that are located further away from the carbonaceous substrate. Without wishing to be bound by theory, it is believed that higher temperatures increase the reaction kinetics at the surface of the coating. Specifically, the reaction kinetics at the surface may increase more significantly compared to the diffusion kinetics of carbon. In addition, the metallic tantalum may be increased by TaCl5 and / or other TaCl x The substance is located on the coating due to self-decomposition at higher temperatures. Surprisingly, it was found that two annealing methods can be used to increase the proportion of TaC in the tantalum carbide coating and / or reduce the proportion of Ta2C and metallic tantalum. TaC (also known as tantalum monocarbide) and Ta2C (also known as tantalum semicarbide) may exhibit different properties. Specifically, TaC may exhibit increased hardness compared to Ta2C and metallic tantalum. In addition, TaC is chemically more stable than Ta2C. For example, in a SiC epitaxial growth process, Ta and Ta2C residues in the coating may react with the carbonaceous precursor used for SiC growth, which in turn may change the reaction kinetics of the process, leading to poor process results. In addition, Ta2C and Ta may react with other process gases (such as Cl2 or HC1), which may lead to degradation of the coating characteristics.

[0111] In some embodiments, the annealing step may include placing the coated carbonaceous substrate in an annealing chamber, heating the annealing chamber to a temperature between about 900°C and about 1800°C, more specifically 1200°C and about 1500°C, for a duration of about 10 minutes to about 5 hours, and supplying a process gas to the reaction chamber, wherein the process gas may contain a carbonaceous substance, more specifically a substance containing carbon and hydrogen, and in particular C2H4. The carbonaceous substance may provide carbon to the tantalum carbide coating to form TaC from Ta2C and metallic tantalum. In addition, the elevated temperature may also allow carbon to diffuse from the carbonaceous substrate to the tantalum carbide coating at a higher rate.

[0112] In another embodiment, the annealing step may include placing the coated carbonaceous substrate in an annealing chamber and heating the reaction chamber to a temperature between about 1900°C and about 2300°C under an inert gas atmosphere for a duration of about 0.5 hours to about 3 hours. The annealing step may be performed at a temperature of about 1900°C to about 2300°C without providing carbon to the process gas. Without being bound by theory, it is believed that a temperature range of about 1900°C to about 2300°C can significantly increase the mobility or diffusion rate of carbon in the tantalum carbide coating. Therefore, carbon can move from a carbon-rich portion of the carbonaceous substrate and / or the tantalum carbide coating to a carbon-poor portion of the tantalum carbide coating.

[0113] In addition, the tantalum carbide in the tantalum carbide coating may form tantalum carbide grains. The annealing process performed at a temperature between about 1900°C and about 2300°C may result in an increase in the grain size of the tantalum carbide grains. As a result, the number of grain boundaries and / or the absolute length of the grain boundaries in the tantalum carbide coating may be reduced, which may result in a reduction in the gas permeability of the tantalum carbide coating. The reduced gas permeability may result in improved protection of the carbonaceous material from chemical attack.

[0114] In some embodiments, the method may be performed under a continuous flow of the process gas. A continuous flow process may result in a higher growth rate of the tantalum carbide layer compared to a static atmosphere.

[0115] In some embodiments, the reaction chamber may be sealed or semi-sealed. In some embodiments, the reaction chamber may be placed in a process unit. The process unit may be sealed. In an unsealed reaction chamber, such as a reaction chamber with a continuous flow of process gas, the process gas enters the reaction chamber through an inlet and subsequently exits the reaction chamber after at least partially reacting with the carbonaceous substrate. For example, Cl2 or HCl may enter the reaction chamber through an inlet and react with tantalum metal powder placed in the reaction chamber to form TaCl5 and / or other TaCl x Then, TaCl5 and / or other TaCl x substances can react with the carbonaceous substrate to form a tantalum carbide coating and Cl2. However, not all TaCl5 and / or other TaCl x The materials can react with the carbonaceous substrate and may be transported out of the reaction chamber, resulting in the loss of relatively expensive tantalum. The sealed reaction chamber or sealed process unit is used in such a way that HC1 or Cl2 is provided to the reaction chamber or the surrounding process unit through the gas inlet at the beginning of the reaction, and then the flow of process gas is stopped and the gas inlet and outlet are closed. HC1 or Cl2 can then react with the provided solid tantalum metal (especially tantalum metal powder) to form TaCl5 and / or other TaCl xsubstances, which can react again with the carbonaceous substrate to form a tantalum carbide coating. Since the reaction chamber or process unit is sealed, there is no unreacted TaCl5 and / or other TaCl x The material leaves the reaction chamber, thus preventing the loss of tantalum. However, the growth of the tantalum carbide coating can continue, because when TaCl5 and / or other TaCl x The Cl2 formed when the substance reacts with the carbonaceous substrate can react again with the solid tantalum metal to form TaCl5 again. Therefore, the yield of tantalum can be increased.

[0116] Similarly, when using solid TaCl5 placed in a reaction chamber as a precursor, a sealed reaction chamber setup or process unit can also be used. In this setup, the process gas can be formed directly in the reaction chamber by heating the reaction chamber. By keeping the reaction chamber or process unit sealed, no TaCl5 and / or other TaCl x The material can leave the reaction chamber and TaCl5 and / or other TaCl x The substance can only react with the carbonaceous substrate to form a tantalum carbide coating. Therefore, the yield of tantalum can be increased.

[0117] In the semi-sealed reaction chamber, a continuous flow of process gas can flow around the reaction chamber, for example, within a process unit. Part of the process gas, especially the halide-containing species, can enter the semi-sealed reaction chamber to react with the solid tantalum metal to form TaCl x Since the reaction chamber is semi-sealed, the halide-containing substances and the formed TaCl x The residence time can be increased, which can lead to higher tantalum yields because less tantalum is lost to the waste stream compared to an open setup.

[0118] The process unit and / or the reaction chamber may include an agitator configured to agitate the gases within the process unit and / or the reaction chamber. For example, the process unit and / or the reaction chamber may include a fan. The agitator may increase the growth rate of the tantalum carbide coating, for example by reducing dead zones, which may form, for example, in the corners of the process unit and / or the reaction chamber. In addition, the gas exchange rate at the surface of the carbonaceous surface may be increased, which may also increase the reaction rate. As described above, at the surface of the carbonaceous substrate, the tantalum halide (e.g., TaCl x ) can react with the carbonaceous substrate to form TaC and a halide (e.g., Cl2). For example, the agitator can increase the amount of Cl2 on the surface of the carbonaceous substrate to be converted to TaCl x The rate of substitution. Then TaCl x can react with the carbonaceous substrate again. In addition, due to the action of the agitator, the Cl2 can contact the solid tantalum metal (if present) more quickly to form TaCl again. x .

[0119] Substrate

[0120] In a second aspect, the present disclosure is directed to a carbonaceous substrate comprising a first tantalum carbide coating, wherein the first tantalum carbide coating is located on an outer surface of the carbonaceous substrate, and wherein the carbonaceous substrate comprises a plurality of pores, the plurality of pores comprising the tantalum carbide porous coating, wherein the plurality of pores are not completely filled with the tantalum carbide porous coating.

[0121] In some embodiments, the plurality of pores may be arranged to be less than 182 μm, in particular less than 100 μm from the outer surface. It should be noted that pores may exist in a portion of the carbonaceous material that is farther from the outer surface than 182 μm or 100 μm. However, pores farther from the outer surface may not be relevant to the anchoring of the first tantalum carbide coating. In addition, pores farther from the outer surface may not be in significant contact with the tantalum halide material, and therefore may not show a significant tantalum carbide porous coating after the coating process.

[0122] In some embodiments, the thickness of the tantalum carbide porous coating may be less than 20 μm, more specifically less than 10 μm, and especially less than 8 μm.

[0123] In some embodiments, the thickness of the tantalum carbide porous coating layer having a depth between about 20 μm and about 60 μm can be between about 0.5 μm and about 8 μm, more specifically between about 0.8 μm and about 3 μm, and in particular between about 1 μm and about 2.5 μm. As described above, excessive thickness of the tantalum carbide porous coating layer may cause local damage to the carbonaceous substrate due to expansion of the tantalum carbide at elevated temperatures. However, providing a tantalum carbide porous coating layer having a minimum thickness can improve the anchoring of the first tantalum carbide coating layer to the carbonaceous substrate and increase the resistance of the pores to chemical attack.

[0124] In some embodiments, the ratio of the thickness of the first tantalum carbide coating to the thickness of the tantalum carbide porous coating having a depth between about 20 μm and about 60 μm can be between about 2:1 and about 30:1, more specifically between about 3:1 and about 20:1, and in particular between about 5:1 and about 15:1. The term "depth" is well known and has, among other things, its common meaning in the art. Additionally or alternatively, the term "depth" can refer to a direction extending into the bulk of a material along a direction perpendicular to an outer surface of the material.

[0125] The thickness of the tantalum carbide porous coating at a depth between about 20 μm and about 60 μm can be measured by the following protocol:

[0126] a) Creating an SEM overview image showing a depth of the substrate between about 20 μm and about 60 μm. The width of the created SEM overview image is selected so that at least 30 pores having a maximum diameter of at least 5 μm are present. The SEM overview image may consist of a plurality of SEM images placed side by side with each other,

[0127] b) identifying all pores with a maximum diameter of at least 5 μm in the SEM overview image as a subset of pores,

[0128] c) determining the thickness of the tantalum carbide pore coating perpendicular to the underlying carbonaceous substrate at five locations equally spaced along the circumference of each pore in the pore subset,

[0129] d) calculating the thickness of the tantalum carbide porous coating by averaging the tantalum carbide porous coating thicknesses determined in step c) at all 5 locations of all holes of the subset of holes.

[0130] It has been found that the above method can allow the coating of pores with smaller maximum diameters than known methods. In some embodiments, the maximum diameter of the plurality of pores may be between about 5 μm and about 100 μm, more specifically between about 10 μm and about 50 μm, and in particular between 15 μm and about 25 μm. The pores in the carbonaceous substrate may also exhibit smaller or larger diameters, however, these should not be considered as belonging to the plurality of pores defined herein. However, the volume of the plurality of pores may account for at least 50%, more specifically at least 75%, and in particular at least 90% of the total volume of pores less than 182 μm, particularly less than 100 μm from the outer surface. The volume of the tantalum carbide porous coating should be considered as part of the pore volume of the plurality of pores. Compared to larger pores, given the same proportion of pore volume, smaller pores can improve the anchoring of the first tantalum carbide coating by providing more anchoring sites. However, if there are a large number of pores less than 5 μm, these pores may be overfilled by the tantalum carbide porous coating, which may lead to partial destruction of the above-mentioned carbonaceous substrate. As mentioned previously, the method according to the first aspect may allow for coating of pores having a smaller maximum diameter with a tantalum carbide pore coating compared to known methods.

[0131] In some embodiments, at least 50%, more specifically at least 75%, and especially at least 90% of the plurality of pores exhibiting a maximum diameter between about 5 μm and about 100 μm may not be completely filled with tantalum carbide, especially at a depth between about 20 μm and about 60 μm. Some of the plurality of pores, especially the pores near the outer surface, may be completely filled with the tantalum carbide pore coating.

[0132] In some embodiments, the volume of the plurality of pores in the carbonaceous substrate may be between about 1% to about 20% by volume, more specifically between about 5% to about 15% by volume, and particularly between about 7% to about 13% by volume. A substrate having a higher porosity may improve the anchoring of the first tantalum carbide coating.

[0133] However, carbonaceous substrates with lower porosity can exhibit improved mechanical properties. In addition, carbonaceous substrates with lower pore volume, particularly isostatic graphite, can exhibit smaller pore sizes, which may improve anchoring as described above. However, carbonaceous substrates with higher pore volume, particularly isostatic graphite, can be produced. In some embodiments, the carbonaceous substrate can therefore include a plurality of pores of about 7% by volume to about 20% by volume, wherein at least 50%, more specifically at least 75%, and particularly at least 90% of the pores in the plurality of pores have a maximum diameter between about 5 μm and about 100 μm.

[0134] In some embodiments, the carbonaceous substrate may include TaC with a penetration depth of at least 20 μm, more specifically at least 40 μm, and especially at least 60 μm. As previously described, the above method can allow the tantalum halide species to penetrate deeper into the carbonaceous substrate, thereby improving the anchoring of the first tantalum carbide coating and the chemical resistance of the carbonaceous substrate.

[0135] In some embodiments, the first tantalum carbide coating and / or the tantalum carbide porous coating may have a ratio of Ta to C between about 1.3:1 and about 1:1.3, more specifically between about 1.1:1 and about 1:1.1, and in particular between about 1.05:1 and about 1:1.05. As described above, it was surprisingly found that coating a carbonaceous substrate using the process parameters of the first coating step can produce a tantalum carbide coating in which the ratio of tantalum to carbide is close to 1. In addition, a tantalum coating primarily comprising TaC can exhibit improved properties, such as increased mechanical hardness and chemical resistance as described above, compared to Ta2C or metallic tantalum. Coatings that contain more carbon than tantalum, for example, may contain crystalline graphite domains, which may also exhibit reduced mechanical properties and chemical resistance.

[0136] In some embodiments, the thickness of the first tantalum carbide coating may be between about 0.1 μm and about 40 μm, more preferably between about 5 μm and about 35 μm, and particularly between about 10 μm and about 30 μm. The thickness of the first tantalum carbide coating may be determined perpendicular to the outer surface.

[0137] The tantalum carbide coating is typically present in crystalline form. The tantalum carbide layer prepared by the method of the first aspect may exhibit a characteristic distribution of tantalum carbide crystals measured by X-ray diffraction. Specifically, the method of the first aspect may produce a tantalum carbide layer comprising tantalum carbide crystals, wherein the tantalum carbide crystals do not exhibit a preferred orientation, and thus the orientation of the tantalum carbide crystals is primarily random. Thus, in some embodiments, the first tantalum carbide coating may comprise tantalum carbide in the form of tantalum carbide crystals, wherein each tantalum carbide crystal orientation in the group

[111] ,

[200] ,

[220] ,

[311] , and

[311] exhibits a texture coefficient TC between about 0.5 and about 1.5. i , the texture coefficient TC i It is calculated from the maximum peak intensity of the X-ray diffraction pattern detected with Cu k-α radiation at a wavelength of 1.5406 Å according to the following formula:

[0138]

[0139] Among them I i Accordingly, the maximum intensity of the crystal orientation is selected,

[0140] Where n=5, and

[0141] I 111 is the maximum intensity at 2θ ranging from 33.9° to 35.9°,

[0142] I 200 is the maximum intensity at 2θ ranging from 39.4° to 41.4°,

[0143] I 220 is the maximum intensity at 2θ ranging from 57.6° to 59.6°,

[0144] I 311 is the maximum intensity at 2θ ranging from 69.0° to 71.0°,

[0145] I 222 is the maximum intensity at 2θ ranging from 72.6° to 74.6°,

[0146] And wherein if the crystal orientation of the tantalum carbide crystals is random, then I i,0 is the expected strength for this crystal orientation.

[0147] Tantalum carbide coatings exhibiting substantially random crystal orientation may exhibit increased chemical resistance.

[0148] Tantalum carbide coatings comprising substantially random crystal orientations can also be produced, for example, by sintering tantalum carbide particles on a substrate surface. However, tantalum carbide coatings formed by sintering may be porous. In order to reduce the porosity, sintering aids may be mixed with the tantalum carbide particles. However, sintering aids may introduce unwanted impurities into the tantalum carbide coating.

[0149] In some embodiments, the porosity of the first tantalum carbide layer may be less than 5 volume %, more specifically less than 1 volume %, and particularly less than 0.1 volume %.

[0150] In some embodiments, the first tantalum carbide layer may contain less than 1 atomic %, more specifically less than 0.1 atomic %, and especially less than 0.01 atomic % impurities. The term "impurities" in this disclosure shall mean elements other than tantalum and carbon.

[0151] In some embodiments, the distribution of tantalum carbide crystal orientations may exhibit a texture coefficient between about 0.35 and about 0.6, more specifically between about 0.35 and about 0.55, and especially between about 0.4 and about 0.52.

[0152] In some embodiments, the carbonaceous substrate comprises, consists essentially of, or consists of graphite, particularly isostatic graphite. As described above, graphite can exhibit high temperature resistance, high melting point, high thermal conductivity, and low thermal expansion coefficient, and can therefore be used in many high temperature processes. In addition, graphite can be used as a susceptor and can exhibit relatively high chemical purity. In addition, graphite is primarily composed of carbon, and thus can provide carbon for forming a first tantalum carbide coating and a tantalum carbide porous coating. Specifically, isostatic graphite can have improved mechanical properties compared to other types of graphite (e.g., extruded or vibration-formed graphite). In addition, isostatic graphite can have pores with a smaller average maximum pore size. As described above, the methods described herein can allow coating of pores with a smaller maximum pore size, thereby allowing the first tantalum carbide coating to be anchored into the isostatic graphite.

[0153] The term "graphite" is well known and has its common meaning in the art. More specifically, the term "graphite" may refer to a material comprising crystalline carbon in a hexagonal structure. Alternatively or additionally, the term "graphite" may refer to a material comprising at least about 60 atomic %, more specifically at least about 80 atomic %, and in particular at least about 83 atomic % of crystalline carbon in a hexagonal structure. Alternatively or additionally, the term "graphite" may refer to a material having a degree of graphitization of at least about 46 atomic %, more specifically 69 atomic %, even more specifically at least about 80 atomic %, and in particular at least about 83 atomic %.

[0154] The degree of graphitization of carbonaceous substrates can be measured by XRD. The crystalline carbon in graphite forms multiple honeycomb lattices. XRD can be used to measure the interplanar distance d between multiple lattices. 001 Thus, the term "graphite" may additionally or alternatively refer to a carbonaceous material, wherein the interplanar distance of the carbonaceous material is between about 0.3400 and about 0.3354, more specifically between 0.3381 and about 0.3354, even more specifically between about 0.3371 and about 0.3354, and particularly between about 0.3369 and about 0.3354. In order to perform XRD measurements on a graphite substrate according to the present disclosure, the tantalum carbide coating and the tantalum carbide pore coating must be removed and the measurement performed using only the underlying carbonaceous material.

[0155] The interplanar distance can also be used to calculate the degree of graphitization using the following formula:

[0156]

[0157] 0.3340 corresponds to the interplanar distance of turbostratic graphite, while 0.3354 corresponds to the interplanar distance in a perfect graphite crystal.

[0158] In some embodiments, the carbonaceous substrate may exhibit a degree of graphitization between about 46 atomic % and about 83 atomic %, more specifically between about 46 atomic % and about 69 atomic %. The thermal expansion coefficient of the less graphitized graphite may be closer to the thermal expansion coefficient of tantalum carbide than the more graphitized graphite. Therefore, the less graphitized graphite may provide the carbonaceous substrate with greater thermal stability.

[0159] In some embodiments, the carbonaceous substrate may include carbon fiber reinforced carbon, CFRC, more specifically, wherein the carbonaceous substrate may include at least about 90% by weight of CFRC relative to the total weight of the carbonaceous substrate, and in particular wherein the carbonaceous substrate may include at least about 99% by weight of CFRC. Compared with other carbonaceous substrates, CFRC can exhibit improved mechanical properties. In addition, CRFC is also mainly composed of carbon, so carbon can be provided to form a first tantalum carbide coating and a tantalum carbide pore coating. The term "CFRC" is well known and belongs to its common meaning in the art. More specifically, the term "CFRC" may refer to a composite material of carbon fibers contained in a graphite matrix. Specifically, the term "CFRC" may refer to a composite material consisting of carbon fibers in a graphite matrix.

[0160] In some embodiments, the carbonaceous substrate may include a second tantalum carbide coating, wherein the second tantalum carbide coating may be arranged adjacent to the first tantalum carbide coating, in particular wherein the first tantalum carbide coating may be located between the second tantalum carbide coating and the outer surface of the carbonaceous substrate. The second tantalum carbide coating may be located on the first tantalum carbide coating. For example, the first tantalum carbide coating may be formed by a first coating step. Subsequently, the second tantalum carbide coating may be deposited on the first tantalum carbide coating using a second or third coating step. The first tantalum carbide coating may be formed on the carbonaceous substrate by the first coating step to achieve improved anchoring and only partial filling of multiple pores. However, it may be preferred to have a tantalum carbide layer having a greater thickness than that provided by the first tantalum carbide coating on the outer surface of the carbonaceous substrate, for example to improve the mechanical properties and chemical resistance of the carbonaceous substrate. However, as described above, as the thickness of the first tantalum carbide coating increases, the growth of the first tantalum carbide coating by the first coating step may be greatly slowed down. Therefore, at elevated temperatures and / or when an additional carbon source is used in the process gas, the second or third coating step may be used to increase the total thickness of the tantalum carbide coating provided on the carbonaceous substrate. The properties of the second tantalum carbide coating may be different from the properties of the first tantalum carbide coating. For example, the second tantalum carbide coating may exhibit a different tantalum and carbon stoichiometry and / or a different tantalum carbide crystal orientation. However, the second tantalum carbide coating may also be epitaxially grown on or aligned with the first tantalum carbide coating during the annealing step, thereby exhibiting the above-mentioned tantalum carbide crystal orientation. In addition, as described above, the annealing step may also shift the tantalum to carbon stoichiometry toward carbon, so that the second tantalum carbide coating may then also exhibit a tantalum to carbon stoichiometric ratio close to 1.

[0161] use

[0162] In a third aspect, the present disclosure relates to the use of a carbonaceous substrate according to any of the preceding items, wherein the carbonaceous substrate is used as a component of an epitaxial growth system, more specifically as a component of a GaN or SiC growth system, and in particular as a wafer carrier for a GaN or SiC growth system; or, as a component of a physical vapor transport system (PVT), more specifically as a component of a SiC PVT system for growing SiC single crystals, and in particular as a crucible or hot wall for a PVT system.

[0163] In a fourth aspect, the present disclosure relates to a method for annealing a carbonaceous substrate including a tantalum carbide coating. The annealing step according to the fourth aspect comprises placing the coated carbonaceous substrate in an annealing chamber, heating the annealing chamber to a temperature between about 900°C and about 1800°C for a duration of about 10 minutes to about 5 hours, and supplying a process gas to the reaction chamber, wherein the process gas comprises a carbonaceous substance, more specifically a carbon and hydrogen substance, and in particular C2H4.

[0164] In a fifth aspect, the present disclosure relates to a method for annealing a carbonaceous substrate including a tantalum carbide coating. The annealing step according to the fifth aspect comprises placing the coated carbonaceous substrate into an annealing chamber and heating the chamber to a temperature between about 1900°C and about 2300°C under an inert gas atmosphere for a duration of about 0.5 hours to about 3 hours. DETAILED DESCRIPTION

[0165] Experimental Section

[0166] Sample preparation

[0167] For each of the following examples, a graphite substrate was used. The graphite used was isostatic graphite grade R6810, available from SGL Carbon GmbH, Germany. The dimensions of the cuboid graphite substrate were 10 cm x 6 cm x 0.15 cm.

[0168] Experimental setup

[0169] The following examples were all carried out in a laboratory-scale low-pressure CVD reactor. The CVD reactor comprises a cell with a gas inlet and outlet arranged opposite to each other. The reaction chamber itself is placed in the cell and comprises an inductively heated graphite susceptor with dimensions of 20 cm × 8 cm × 2 cm. Time series tests were performed by placing four graphite samples in the reaction chamber and removing one sample after a quarter of the total process duration had passed.

[0170] First experiment

[0171] The setup for the first experiment can be found in Figure 1 In the first experiment, tantalum metal powder (140) was loaded into the reaction chamber (100). A graphite substrate (130) was placed next to the metal powder (140), wherein the graphite substrate (130) was placed in the downstream direction of the metal powder (140). The unit and the reaction chamber (100) were then evacuated and the susceptor was heated under a gas flow (110) of argon (Ar) as a carrier gas until the temperature reached 1200°C. When the temperature reached 1200°C, HCl was added to the gas flow (110) to form the process gas. The flow rate of Ar was 1000 standard cubic centimeters and the flow rate of HCl was 100 standard cubic centimeters. The reaction chamber was not sealed; therefore the process gas was able to leave the reaction chamber (100) as exhaust gas (120). The pressure in the reaction chamber (100) was maintained at 150 millibars and the reaction was carried out for 3 hours.

[0172] The thickness of the obtained tantalum carbide coating is 3.7 μm. Figure 2 As shown in Fig. 2a and 2c, the obtained coating surface is dense and smooth.

[0173] The X-ray diffraction results of the coated samples are shown in Table 1.

[0174] Table 1 Crystalline plane TC measured by X-ray diffraction patterns

[0175]

[0176] As can be seen from Table 2, the tantalum carbide coating does not show a clear preferred crystal orientation.

[0177] Second experiment

[0178] The setup of the second experiment corresponds to that of the first experiment. In the second experiment, the temperature was increased to 1300 °C and all other parameters remained constant.

[0179] The thickness of the resulting tantalum carbide coating was 3.3 μm. It was found that the use of higher temperatures resulted in the formation of a hard crust on the tantalum metal powder, which may have reduced the growth rate of the tantalum carbide coating compared to lower temperatures. Therefore, when using tantalum metal powder, the coating method can use lower temperatures. Figure 2 As shown in Figs. 2a and 2b, the coating surface is dense and smooth. The size of the tantalum carbide crystals obtained in the second experiment is larger than that obtained in the first experiment.

[0180] The X-ray diffraction results of the coated samples are shown in Table 2.

[0181] Table 2 Crystalline plane TC measured by X-ray diffraction patterns

[0182]

[0183] As can be seen from Table 2, the tantalum carbide coating does not show a clear preferred crystal orientation.

[0184] The third experiment

[0185] In the third experiment, a semi-sealed reaction chamber was used. The setup for the third experiment can be found in Figure 4 As seen in . Similarly, tantalum metal powder (240) is loaded into the reaction chamber (200). A graphite substrate (230) is placed above the tantalum metal powder (240) and supported by four graphite felt supports (250). The unit and the reaction chamber (200) are evacuated and then heated to a temperature of 1300°C under a flow of 1000 standard cubic centimeters of Ar at a pressure of 150 mbar. When the temperature of 1300°C is reached, a flow rate of 1000 standard cubic centimeters of Ar and 100 standard cubic centimeters of HCl are applied as process gases at a pressure of 150 mbar. The reaction is carried out for 3 hours. As Figure 4As shown, the process gas (210) flows around a semi-sealed reaction chamber within the unit. However, a portion of the gas flow (210) may enter the semi-sealed reaction chamber and react with the tantalum metal powder to form TaCl before exiting as exhaust gas (220). x substance.

[0186] It is believed that in this setting, TaCl x After reacting with graphite, the generated Cl2 will react again with tantalum metal powder to form TaCl again. x .

[0187] The thickness of the obtained tantalum carbide coating is 3.7 μm. Figure 5 As shown in b, the coating surface is dense and smooth. Figure 5 As shown in a, cracks were observed. Figure 3 c shows that the hole is only partially coated.

[0188] The X-ray diffraction results of the coated samples are shown in Table 3.

[0189] Table 3 Crystalline plane TC measured by X-ray diffraction pattern

[0190]

[0191] As can be seen from Table 3, the tantalum carbide coating does not show a clear preferred crystal orientation.

[0192] The fourth experiment

[0193] In the fourth experiment, a sealed process unit with a semi-sealed reaction chamber was used. The test setup corresponds to that of the third experiment and can therefore be Figure 4 . The tantalum metal powder is again loaded into the reaction chamber and a graphite substrate is placed above the tantalum metal powder, supported by four graphite felt supports. The reaction chamber and the process unit are evacuated and subsequently the process unit is filled with Ar at a flow rate of 1000 standard cubic centimeters and HCl at a flow rate of 100 standard cubic centimeters until a pressure of 150 mbar is reached. The gas inlet and outlet of the process unit are then closed to form a sealed process unit. Process gases including HCl can enter the semi-sealed reaction chamber again. Subsequently, the reaction chamber is heated to a temperature of 1200°C for 3 hours to carry out the coating step.

[0194] The thickness of the obtained tantalum carbide coating is 1.5 μm. Figure 6 As shown in b, the coating is dense. Figure 6 As shown in a, cracks were observed. Figure 3 As shown in b, the pores are only partially coated.

[0195] The X-ray diffraction results of the coated samples are shown in Table 4.

[0196] Table 4 Crystalline plane TC measured by X-ray diffraction pattern

[0197]

[0198] As can be seen from Table 4, the tantalum carbide coating does not show a clear preferred crystal orientation.

[0199] The fifth experiment

[0200] In the fifth experiment, a sealed process unit with a semi-sealed reaction chamber was used. The test setup was the same as in the fourth experiment. However, in the fifth experiment, a mixture of tantalum metal powder and TaCl5 was loaded into the reaction chamber, and a graphite substrate was placed above the powder mixture, supported by four graphite felt supports. The reaction chamber and the process unit were evacuated and subsequently, the process unit was filled with only Ar at a flow rate of 1000 standard cubic centimeters until a pressure of 150 mbar was reached. No HCl or other gaseous halide sources were added. The gas inlet and outlet of the process unit were then closed to form a sealed process unit. Subsequently, the reaction chamber was heated to a temperature of 1300°C for 3 hours to carry out the coating step.

[0201] During this process, both the TaCl5 powder and the tantalum metal powder reacted with the graphite substrate. It is believed that the TaCl5 powder evaporated and reacted with the graphite substrate to form tantalum carbide, while releasing Cl2, which then reacted with the tantalum metal powder to form TaCl again. x .

[0202] The thickness of the obtained tantalum carbide coating is 2.2 μm. Figure 7 As shown in Figs. a and 7b, the coating is dense. Figure 3 As shown in a, the hole is only partially coated.

[0203] The X-ray diffraction results of the coated samples are shown in Table 5.

[0204] Table 5 Crystalline plane TC measured by X-ray diffraction pattern

[0205]

[0206] As can be seen from Table 5, the tantalum carbide coating does not show a clear preferred crystal orientation.

[0207] The sixth experiment

[0208] The setup of the sixth experiment is the same as the first experiment. Therefore, the setup of the sixth experiment can be found in Figure 1As seen in Figure 2. In contrast to the first experiment, the reaction chamber was not loaded with tantalum metal powder. The cell and the reaction chamber were evacuated and the susceptor was heated under a gas flow of argon (Ar) as a carrier gas until a temperature of 1300°C was reached. When the temperature reached 1300°C, TaCl5 was added to the gas flow to form the process gas. The flow rate of Ar was 1000 standard cubic centimeters. The flow rate of TaCl5 was about 5 standard cubic centimeters. TaCl5 was generated in an external evaporator. The reaction chamber was not sealed so that the process gas was able to leave the reaction chamber as exhaust gas. The pressure in the reaction chamber was maintained at 150 mbar and the reaction was carried out for 12 hours.

[0209] The thickness of the obtained tantalum carbide coating is 8.8 μm. Figure 8 As shown in b, the coating surface is dense and smooth. Figure 8 As shown in a, cracks also appear in the coating.

[0210] The X-ray diffraction results of the coated samples are shown in Table 6.

[0211] Table 6 Crystalline plane TC measured by X-ray diffraction pattern

[0212]

[0213] As can be seen from Table 6, the tantalum carbide coating does not show a clear preferred orientation.

[0214] This process can obtain high-purity TaC coatings, such as Fig.13 shown.

[0215] The seventh experiment

[0216] In the seventh experiment, the same setup as the sixth experiment was used. However, the temperature was set to 1500°C. Four samples were placed in the reaction chamber and one sample was taken out every 3 hours and analyzed. The coating thickness was 35 μm after 12 hours of the coating method. However, as the coating thickness increased, the stoichiometry of the coating changed from TaC to Ta2C and Ta. The changes in the ratios of Ta2C, Ta and TaC were determined by X-ray diffraction measurements on the four samples. The X-ray diffraction results are shown in Figure 2. Fig.10 shown.

[0217] The eighth experiment

[0218] In the eighth experiment, the effect of annealing at 2100°C without a carbon source was tested. The samples of experiments three, four, six and seven were annealed in an annealing furnace in an Ar atmosphere at a temperature of 2100°C for 1 hour.

[0219] Fig. 9 a, c, e, and g show the samples before annealing. Fig. 9 b, d, f, h show the samples after annealing. Fig. 9 a, 9b show samples from the third experiment, which were coated before and after annealing at 2100°C for 3 hours. Fig. 9 c, 9d show samples from the fourth experiment, coated before and after annealing at 2100°C for 3 hours. Fig. 9 e, 9f show samples from the sixth experiment, coated before and after annealing at 2100°C for 12 h. Fig. 9 g, 9h show the samples of the seventh experiment, coated before and after annealing at 2100°C for 6 hours. Fig. 9 As can be seen, as the crystal size increases, the number of grain boundaries decreases.

[0220] In addition, annealing of the sample from the seventh experiment resulted in the conversion of Ta2C and Ta species into TaC, resulting in a pure TaC coating. The X-ray diffraction results after the eighth experiment are shown in Figure 2. Fig.14 and 15 shown.

[0221] Ninth Experiment

[0222] In the ninth experiment, the effect of annealing at 1200°C with an additional carbon source was tested. The sample from the seventh experiment was annealed in an annealing furnace in an Ar and C2H4 atmosphere at 1200°C for 10 minutes. The flow rate of Ar was 5000 standard cubic centimeters and the flow rate of C2H4 was 25 standard cubic centimeters. Annealing resulted in the conversion of Ta2C and Ta species to TaC, resulting in a pure TaC coating. The X-ray diffraction results of the ninth experiment are shown in Figure 1. Fig.16 shown.

[0223] Although the present invention is defined in the claims, it should be understood that the present invention may also (alternatively) be defined according to the following embodiments:

[0224] 1. A carbonaceous substrate comprising a first tantalum carbide coating,

[0225] wherein the first tantalum carbide coating is located on the outer surface of the carbonaceous substrate,

[0226] And wherein the carbonaceous substrate comprises a plurality of pores, the plurality of pores comprises a tantalum carbide porous coating, wherein the plurality of pores are not completely filled with the tantalum carbide porous coating.

[0227] 2. The carbonaceous substrate according to any one of the preceding claims, wherein the plurality of pores is arranged less than 182 μm, in particular less than 100 μm, from the outer surface.

[0228] 3. The carbonaceous substrate according to any one of the preceding claims, wherein the tantalum carbide porous coating has a thickness of less than 20 μm, more particularly less than 10 μm, and especially less than 8 μm.

[0229] 4. The carbonaceous substrate according to any one of the preceding claims, wherein the tantalum carbide porous coating has a thickness of between about 0.5 μm and about 8 μm, more specifically between about 0.8 μm and about 3 μm, and in particular between about 1 μm and about 2.5 μm to a depth of between about 20 μm and about 60 μm.

[0230] 5. The carbonaceous substrate according to any one of the preceding claims, wherein the ratio of the thickness of the first tantalum carbide coating layer to the thickness of the tantalum carbide porous coating layer having a depth of between about 20 μm and about 60 μm is between about 2:1 and about 30:1, more specifically between about 3:1 and about 20:1, and especially between about 5:1 and about 15:1.

[0231] 6. The carbonaceous substrate according to any one of the preceding claims, wherein the plurality of pores has a maximum diameter between about 5 μm and about 100 μm, more specifically between about 10 μm and about 50 μm, and especially between 15 μm and about 25 μm.

[0232] 7. The carbonaceous substrate according to any one of the preceding claims, wherein among a plurality of pores exhibiting a maximum diameter between about 5 μm and about 100 μm, at least 50%, more specifically at least 75% and especially at least 90% of the pores are not completely filled by the tantalum carbide porous coating.

[0233] 8. The carbonaceous substrate according to any one of the preceding claims, wherein the volume of the plurality of pores in the carbonaceous substrate is between about 1 vol % and about 20 vol %, more specifically between about 5 vol % and about 15 vol %, and especially between about 7 vol % and about 13 vol %.

[0234] 9. The carbonaceous substrate according to any one of the preceding claims, wherein the carbonaceous substrate comprises TaC with a penetration depth of at least 20 μm, more particularly at least 40 μm, and especially at least 60 μm.

[0235] 10. The carbonaceous substrate according to any of the preceding claims, wherein the first tantalum carbide coating and / or the tantalum carbide porous coating has a ratio of Ta to C between about 1.3:1 to about 1:1.3, more specifically between about 1.1:1 to about 1:1.1, and especially between about 1.05:1 to about 1:1.05.

[0236] 11. The carbonaceous substrate according to any one of the preceding claims, wherein the first tantalum carbide coating has a thickness between about 0.1 μm and about 40 μm, more preferably between about 5 μm and about 35 μm, and in particular between about 10 μm and about 30 μm.

[0237] 12. The carbonaceous substrate of any of the preceding claims, wherein the first tantalum carbide coating comprises tantalum carbide in the form of tantalum carbide crystals, wherein each tantalum carbide crystal orientation in the group

[111] ,

[200] ,

[220] ,

[311] , and

[311] exhibits a texture coefficient TC between about 0.5 and about 1.5. i , the texture coefficient TC i It is calculated from the maximum peak intensity of the x-ray diffraction pattern detected with Cu k-alpha radiation at a wavelength of 1.5406 Å according to the following formula:

[0238]

[0239] Among them I i Accordingly, the maximum intensity of the crystal orientation is selected,

[0240] Where n=5, and

[0241] I 111 is the maximum intensity at 2θ ranging from 33.9° to 35.9°,

[0242] I 200 is the maximum intensity at 2θ ranging from 39.4° to 41.4°,

[0243] I 220 is the maximum intensity at 2θ ranging from 57.6° to 59.6°,

[0244] I 311 is the maximum intensity at 2θ ranging from 69.0° to 71.0°,

[0245] I 222 is the maximum intensity at 2θ ranging from 72.6° to 74.6°,

[0246] And wherein if the crystal orientation of the tantalum carbide crystals is random, then I i,0 is the expected strength of the crystal orientation.

[0247] 13. The carbonaceous substrate of any preceding claim, wherein the carbonaceous substrate comprises, consists essentially of, or consists of graphite.

[0248] 14. The carbonaceous substrate according to any one of the preceding claims, wherein the carbonaceous substrate comprises a second tantalum carbide coating, wherein the second tantalum carbide coating is arranged adjacent to the first tantalum carbide coating, in particular wherein the first tantalum carbide coating is arranged between the second tantalum carbide coating and an outer surface of the carbonaceous substrate.

[0249] 15. A vapor deposition method for coating a carbonaceous substrate with a tantalum carbide coating, wherein the method comprises a coating step, the coating step comprising:

[0250] - Place the carbonaceous substrate into the reaction chamber,

[0251] - heating the reaction chamber to a temperature between about 1100°C and about 1500°C for a period of about 1 hour to about 24 hours,

[0252] - supplying a process gas to the reaction chamber, wherein the process gas comprises a halide-containing substance, wherein the process gas comprises less than 4 atomic % carbon and less than 10 volume % H2 within at least 15 minutes after the start of the process, and supplying a tantalum-containing substance to the reaction chamber, or placing a solid comprising tantalum in the reaction chamber; or placing a solid comprising tantalum halide in the reaction chamber.

[0253] 16. The method of claim 15, wherein the solid comprising tantalum comprises tantalum in metallic form, in particular tantalum in the form of tantalum metal powder.

[0254] 17. The method according to claim 15, wherein the tantalum-containing substance and the halide-containing substance are the same, in particular wherein the process gas comprises TaCl5 and / or other TaCl x substance.

[0255] 18. The method of claim 15, wherein the solid containing tantalum halide comprises TaCl5 and / or other TaCl x Tantalum halides in physical form, especially TaCl5 and / or TaCl x Tantalum halide in powder form.

[0256] 19. The method according to any of the preceding claims, wherein the coating step comprises a first coating step and a second coating step, wherein the first coating step is performed at a first temperature and the second coating step is performed at a second temperature, in particular wherein the first temperature is lower than the second temperature.

[0257] 20. The method of claim 20, wherein the first temperature is between about 1150°C and about 1250°C and / or the second temperature is between about 1250°C and about 1350°C.

[0258] 21. The method according to any of the preceding claims, wherein the coating step comprises a third coating step, wherein the third coating step is performed at a third temperature, in particular wherein the third temperature is higher than the first temperature and / or the second temperature.

[0259] 22. The method of claim 21, wherein the third temperature is at least about 1350°C, more specifically between about 1350°C and about 1600°C, and in particular between about 1350°C and about 1450°C.

[0260] 23. The method according to any one of claims 19 or 20 or 21 to 22, when dependent on claim 18, wherein the duration of the first coating step and / or the second coating step is at least about 15 minutes, more particularly between about 30 minutes and about 120 minutes, and in particular between about 45 minutes and about 90 minutes.

[0261] 24. The method according to claim 21 or 22, wherein the duration of the third coating step is at least about 60 minutes, more particularly at least about 180 minutes, and in particular at least about 300 minutes.

[0262] 25. A method according to any one of claims 19 or 20 or 21 to 24, when dependent on claim 18, wherein the process gas in the first coating step contains less than 5 atomic %, more particularly less than 1 atomic % and in particular less than 0.1 atomic % carbon relative to the total number of atoms in the process gas.

[0263] 26. A method according to any one of claims 19 or 20 or 21 to 25, when dependent on claim 18, wherein the process gas in the first coating step comprises less than 4% by volume, more particularly less than 1% by volume and in particular less than 0.1% by volume of H2 relative to the total volume of the process gas.

[0264] 27. A method according to any one of claims 19 or 20 or 21 to 26, when dependent on claim 18, wherein the process gas in the first coating step contains a halide, in particular chlorine, having a maximum ratio of halide to carbon of 1:0.05, more particularly 1:0.01 and in particular 1:0.001.

[0265] 28. A method according to any one of claims 19 or 20 or 21 to 27, when dependent on claim 18, wherein the process gas in the first coating step comprises a halide, in particular chlorine, having a maximum ratio of halide to H2 of 1:0.05, more particularly 1:0.01, and in particular 1:0.001.

[0266] 29. A method according to any one of claims 19 or 20 or 21 to 28, when dependent on claim 18, wherein the process gas in the second coating step comprises more than 0.1 atomic %, more particularly more than 1 atomic %, and in particular more than 5 atomic % carbon relative to the total number of atoms in the process gas.

[0267] 30. The method according to any one of the preceding claims, wherein the halide-containing substance is a chloride-containing substance, more specifically, wherein the chloride-containing substance is Cl2 or HCl, and in particular wherein the halide-containing substance is HCl.

[0268] 31. The method according to any of the preceding claims, wherein the process gas additionally comprises an inert gas, more particularly nitrogen or argon, and in particular argon.

[0269] 32. The method according to any of the preceding claims, wherein the pressure in the reaction chamber is between about 0.001 bar and about 1.1 bar, more specifically between about 0.001 bar and about 0.5 bar, and in particular between about 0.1 bar and about 0.2 bar.

[0270] 33. The method according to any one of the preceding claims, wherein the method additionally comprises an annealing step after the coating step.

[0271] 34. The method of claim 33, wherein the annealing step comprises:

[0272] - placing the coated carbonaceous substrate into an annealing chamber,

[0273] - heating the annealing chamber to a temperature between about 900° C. and about 1800° C. for a period of about 10 minutes to about 5 hours,

[0274] - supplying a process gas to the reaction chamber, wherein the process gas comprises a carbon-containing substance, more particularly a carbon and hydrogen-containing substance, and in particular C2H4.

[0275] 35. The method of claim 33, wherein the annealing step comprises:

[0276] - placing the coated carbonaceous substrate into an annealing chamber,

[0277] - heating the reaction chamber to a temperature between about 1900°C and about 2300°C under an inert gas atmosphere for a duration of about 0.5 hours to about 3 hours.

[0278] use

[0279] Use of a carbonaceous substrate according to any one of claims 1 to 14 as a component of an epitaxial growth system, more particularly as a component of a GaN or SiC growth system, and in particular as a wafer carrier for a GaN or SiC growth system;

[0280] Alternatively, it is used as a component of a physical vapor transport (PVT) system, more particularly as a component of a SiC PVT system for SiC single crystal growth, and in particular as a crucible or hot wall of a PVT system.

Claims

1. A carbonaceous substrate comprising a first tantalum carbide coating, wherein the first tantalum carbide coating is located on the outer surface of the carbonaceous substrate, And wherein the carbonaceous substrate comprises a plurality of pores, the plurality of pores comprises a tantalum carbide porous coating, wherein the plurality of pores are not completely filled with the tantalum carbide porous coating.

2. The carbonaceous substrate of claim 1, wherein the tantalum carbide porous coating having a depth between about 20 μm and about 60 μm has a thickness between about 0.5 μm and about 8 μm, more specifically between about 0.8 μm and about 3 μm, and especially between about 1 μm and about 2.5 μm.

3. The carbonaceous substrate according to any of the preceding claims, wherein the ratio of the thickness of the first tantalum carbide coating layer to the thickness of the tantalum carbide porous coating layer having a depth of between about 20 μm and about 60 μm is between about 2:1 and about 30:1, more specifically between about 3:1 and about 20:1, and especially between about 5:1 and about 15:

1.

4. The carbonaceous substrate according to any of the preceding claims, wherein of the plurality of pores exhibiting a maximum diameter between about 5 μm and about 100 μm, at least 50%, more specifically at least 75% and especially at least 90% of the pores are not completely filled by the tantalum carbide porous coating.

5. The carbonaceous substrate according to any one of the preceding claims, wherein the volume of the plurality of pores in the carbonaceous substrate is between about 1 vol % and about 20 vol %, more specifically between about 5 vol % and about 15 vol %, and especially between about 7 vol % and about 13 vol %.

6. The carbonaceous substrate of any of the preceding claims, wherein the first tantalum carbide coating comprises tantalum carbide in the form of tantalum carbide crystals, wherein each tantalum carbide crystal orientation in the group [111], [200], [220], [311], and [311] exhibits a texture coefficient TC between about 0.5 and about 1.

5. i , the texture coefficient TC i It is calculated from the maximum peak intensity of the X-ray diffraction pattern detected with Cu k-α radiation at a wavelength of 1.5406 Å according to the following formula: Among them I i Accordingly, the maximum intensity of the crystal orientation is selected, Where n=5, and I 111 is the maximum intensity at 2θ ranging from 33.9° to 35.9°, I 200 is the maximum intensity at 2θ ranging from 39.4° to 41.4°, I 220 is the maximum intensity at 2θ ranging from 57.6° to 59.6°, I 311 is the maximum intensity at 2θ ranging from 69.0° to 71.0°, I 222 is the maximum intensity at 2θ ranging from 72.6° to 74.6°, And wherein if the crystal orientation of the tantalum carbide crystals is random, then I i,0 is the expected strength of the crystal orientation.

7. A vapor deposition method for coating a carbonaceous substrate with a tantalum carbide coating, wherein the method comprises a coating step, the coating step comprising: - Place the carbonaceous substrate into the reaction chamber, - heating the reaction chamber to a temperature between about 1100°C and about 1500°C for a period of about 1 hour to about 24 hours, - supplying a process gas to the reaction chamber, wherein the process gas comprises a halide-containing substance, wherein the process gas comprises less than 4 atomic % carbon and less than 10 volume % H2 within at least 15 minutes after the start of the process, and supplying a tantalum-containing substance to the reaction chamber, or placing a solid comprising tantalum in the reaction chamber; or placing a solid comprising tantalum halide in the reaction chamber.

8. The method according to claim 7, wherein the tantalum-containing substance and the halide-containing substance are the same, in particular wherein the process gas comprises TaCl5 and / or other TaCl x substance.

9. The method according to claim 7 or 8, wherein the coating step comprises a first coating step and a second coating step, wherein the first coating step is performed at a first temperature and the second coating step is performed at a second temperature, in particular wherein the first temperature is lower than the second temperature.

10. The method of claim 9, wherein the first temperature is between about 1150°C and about 1250°C and / or the second temperature is between about 1250°C and about 1350°C.

11. The method according to any one of claims 9 or 10, wherein the duration of the first coating step and / or the second coating step is each at least about 15 minutes, more specifically between about 30 minutes and about 120 minutes, and in particular between about 45 minutes and about 90 minutes.

12. The method according to any one of claims 9 to 11, wherein the process gas in the first coating step contains less than 5 atom %, more particularly less than 1 atom % and in particular less than 0.1 atom % carbon relative to the total number of atoms in the process gas.

13. The method according to any one of claims 9 to 12, wherein the process gas in the first coating step comprises less than 4 vol.-%, more particularly less than 1 vol.-%, and in particular less than 0.1 vol.-% H2 relative to the total volume of the process gas.

14. The method according to any one of claims 7 to 13, wherein the pressure in the reaction chamber is between about 0.001 bar and about 1.1 bar, more specifically between about 0.001 bar and about 0.5 bar, and especially between about 0.1 bar and about 0.2 bar.

15. Use of a carbonaceous substrate according to any one of claims 1 to 6 as a component of an epitaxial growth system, more particularly as a component of a GaN or SiC growth system, and in particular as a wafer carrier for a GaN or SiC growth system; Alternatively, it is used as a component of a physical vapor transport (PVT) system, more specifically as a component of a SiC PVT system for growing SiC single crystals, and in particular as a crucible or hot wall of a PVT system.

Citation Information

Cited By

  • Method for in-situ growth of thermal shock resistant tantalum carbide coating on carbon-based substrate

    CN119956319A

  • A method for in-situ growth of thermal shock resistant tantalum carbide coating on a carbon-based substrate

    CN119956319B

  • High-purity porous tantalum carbide ceramic as well as preparation method and application thereof

    CN120136575A

  • A high-purity porous tantalum carbide ceramic and its preparation method and application

    CN120136575B